1986
DOI: 10.3109/01050398609045954
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 2-dB and 5-dB Step Size in Pure-Tone Audiometry

Abstract: With the purpose of comparing test-retest reliability, pure-tone audiometry with a step size of 2 and 5 dB using the ascending technique was performed on two groups of subjects. One group consisted of 10 normal-hearing subjects and the other of 10 subjects with moderate cochlear hearing loss. The statistical analysis of the overall estimation of standard deviation obtained with the different step sizes showed no significant difference in any group. However, at 3 000 and 4 000 Hz in the cochlear group a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…In this study we calculated the CR which is capable of showing a potential agreement between repeated measures (Bland and Altman, 1986). Calculation of the SD of differences of repeated measurements has been used for the assessment of the repeatability of pure tone audiometry (Jerlvall and Arlinger, 1986), but we have not been able to identify previous ANLstudies in which the SD or Bland and Altmans (1986) method for repeatability assessment were used. In a letter to the editor, Nabelek et al (2007) reported that in a study of normal-hearing subjects , individual test-retest ANL differences were up to about 14 dB, which is comparable to our results (table 2 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we calculated the CR which is capable of showing a potential agreement between repeated measures (Bland and Altman, 1986). Calculation of the SD of differences of repeated measurements has been used for the assessment of the repeatability of pure tone audiometry (Jerlvall and Arlinger, 1986), but we have not been able to identify previous ANLstudies in which the SD or Bland and Altmans (1986) method for repeatability assessment were used. In a letter to the editor, Nabelek et al (2007) reported that in a study of normal-hearing subjects , individual test-retest ANL differences were up to about 14 dB, which is comparable to our results (table 2 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has reported good correspondence in the thresholds obtained between the manual and automated methods [4,5]. It was reported that the thresholds obtained with manual audiometry and automated computer-controlled audiometry resulted in a high correlation and the mean threshold difference between the two measurement techniques was less than 1 dB [4].…”
Section: Introductionmentioning
confidence: 95%
“…However, a step-size of 2 dB can be considered based on the degree of accuracy required for measurement of auditory thresholds. It was reported that mean threshold differences between step-sizes of 5 dB and 2 dB measured for frequencies at 0.125, 0.25, 0.5, 1, 2, 3, 4, 6 and 8 kHz was about 1.5 dB lower with a step-size of 2 dB [4]. A measurement method needs to have high sensitivity to detect deterioration in hearing thresholds as early as possible for clinical applications in situations such as hearing conservation programs (HCPs) [4].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations